Estudio de prefactibilidad para la implementación de una cadena de bodegas en la zona Norte de Lima Metropolitana - Medrano Guardamino, Claudia (2021)
The wineries, establishments belonging to the traditional channel in Peru, played an important role during the COVID-19 pandemic. Although at first these businesses were affected little by little, they were able to recover and adapt to the behaviors of consumers and also to the protocols that had to be implemented to continue with the attention to the public. The problem addressed by this research is the lack of establishments that offer products of mass consumption not only going to the place but also via a web page or a phone call, without losing the friendly service that provides a hold of the neighborhood; it is for this reason that it is proposed to implement a string of wineries with different means of payment, delivery, payments of basic services, care, biosecurity and pleasant buying experience in the Area of North Lima, taking as selected districts Comas and Carabayllo. The methodology used in the research was to survey those responsible for household purchases on key points during the purchase process in order to evaluate their behavior. In addition, secondary sources were used to have a wider scope of study. The research demonstrated the feasibility of the project, since there is a market that wants to make purchases in person and virtual near their homes, and with the respective care. For the economic part, the results were NPV = S/177 614,78 and an EIRR = 51,14% and for the Financial one an NPV= S/209 148,22 and an EIRR= 71,46%, the investment being S/284 180. On the social side we can affirm the generation of jobs and finally on the environmental side the implementation was implemented ecological measures, cleaning and recycling protocols.